The Influence of Brand Image and Consumer Lifestyle on Iphone Purchasing Decisions (Case Study on iPhone Users in Bogor City) - Kuraesin, Ecin; Sartika, Rahma Yuliana; Marlina, Asti (INOVATOR, 2024)
This research aimed to investigate how brand image and consumer lifestyle influence purchasing decisions of iPhone users in Bogor City. The study utilized quantitative methods, with the target population being iPhone consumers in the city. Probability sampling, specifically simple random sampling, was employed to select 100 respondents who completed a questionnaire using a Likert scale. The data analysis involved multiple linear regression, T-tests, and an F-test using SPSS. The findings indicated a significant positive impact of brand image (T-test value = 3.342 > t-table 1.98, rejecting Ho1 and accepting Ha1) and consumer lifestyle (T-test value = 3.147 > 1.98, rejecting Ho2 and accepting Ha2) on purchasing decisions. Additionally, the F-test (fcount 14.135 > ftabel 3.09) confirmed a collectively significant influence of brand image and lifestyle on purchasing decisions.